2016
DOI: 10.4103/1117-6806.169818
|View full text |Cite
|
Sign up to set email alerts
|

Management of fistula-in-ano with special reference to ligation of intersphincteric fistula tract

Abstract: Context:The surgical management of fistula-in-ano is still debatable and no clear recommendations have been made available until now. The present study analyses the results of ligation of intersphincteric fistula tract (LIFT) technique in treating fistula-in-ano in particular with recurrence, healing time, and continence status.Aims:LIFT in the management of patients of fistula-in-ano of cryptoglandular origin.Settings and Design:Prospective study.Materials and Methods:This is a prospective study of 52 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
3
16
1
1
Order By: Relevance
“…No patient reported any subjective decrease incontinence after the procedure. 14 Jain et al in their study observed no incontinence or recurrence in follow up period of 12 weeks. 4 Our study is consistent with the study by Jain et al with similar results.…”
Section: Discussionmentioning
confidence: 81%
“…No patient reported any subjective decrease incontinence after the procedure. 14 Jain et al in their study observed no incontinence or recurrence in follow up period of 12 weeks. 4 Our study is consistent with the study by Jain et al with similar results.…”
Section: Discussionmentioning
confidence: 81%
“…16 Also in current study, perineum discharge was the commonest symptom in all cases (100%) and which was either continuous or intermittent in nature as similar to the previous studies. 1,[17][18][19][20][21] Almost all cases had one opening either on one side of midline to right or left and anterior or posterior to the anal opening. Only two cases had 2 openings each in this present series.…”
Section: Resultsmentioning
confidence: 99%
“…Khadia M et al; conducted a prospective study which aimed to LIFT in the management of patients of fistula-in-ano of cryptoglandular origin in 52 patients managed with LIFT technique and results of LIFT technique were compared with other studies in terms of recurrence rate, incontinence rate, and other postoperative complications. 6 A total of 52 patients were studied. Median follow-up was 24 weeks.…”
Section: Discussionmentioning
confidence: 99%